THE USAGE ATTITUDE OF INNOVATIVE ONLINE FOOD ORDERING APPLICATIONS OF EMPLOYEES IN LAEM CHABANG INDUSTRIALS ESTATE, CHONBURI - BUSSABAN, Kraikrit; EMIN, Thanapat; MARTSIRI, Ariya; PONPITAK, Punporn; SARAPHAT, Somboon; Kullachart, Rutcharin (Asian Administration and Management Review, 2023)
The pandemic of Coronavirus resulted in the change of ordering food method. Online ordering food was the new one that was famous in this period. The purposes of this research are 1) to study the usage attitude of online food ordering technology of employees who work at Laem Chabang industrial estate, 2) to study the factors that affect the usage attitude of online food ordering technology of employees who work at Laem Chabang industrial estate. The data were collected through a self-administered survey questionnaire. The target population is employees who work at Laem Chabang industrial estate. Purposive sampling is used for the collection of data from 400 employees. The data were analyzed through multiple regression. The results revealed that 1) perceived ease of use of online food ordering applications has a positive influence on the Perceived usefulness of online food ordering applications with a statistically significant level of 0.05, 2) perceived ease of use of online ordering food applications has a negative influence on Behavioral intention to use of online food ordering application with a statistically significant level of 0.05, 3) perceived usefulness of online food ordering applications has a positive influence on Behavioral intention to use of online food ordering application with a statistically significant level of 0.05.